Respuesta :
Given points:
- (2, -5) and (0, 1)
Find the slope:
- m = (1 - (-5))/(0 - 2) = 6/(-2) = -3
Point - slope form:
- y - (-5) = -3(x - 2) ⇒ y + 5 = -3(x - 2)
Convert into slope- intercept form:
- y = -3x + 6 - 5 ⇒ y = -3x + 1
Convert into standard form:
- 3x + y = 1
[tex]▪▪▪▪▪▪▪▪▪▪▪▪▪ {\huge\mathfrak{Answer}}▪▪▪▪▪▪▪▪▪▪▪▪▪▪[/tex]
let's find slope (m) :
- [tex] \dfrac{y2 - y1}{x2 - x1} [/tex]
- [tex] \dfrac{1 - ( - 5)}{0 - 2} [/tex]
- [tex] \dfrac{6}{ - 2} [/tex]
- [tex] - 3[/tex]
Plugging value of x and y from point (0 , 1) and slope (m) = -3, in general equation of line we will get the value of y - intercept (c)
that is :
- [tex]y = mx + c[/tex]
- [tex]1 = (0 \times - 3) + c[/tex]
- [tex]c = 1[/tex]
y intercept (c) = 1, now let's plug the value of slope(m) and y - intercept (c) in general equation of line to get the required equation of line which passes from given two points.
- [tex]y = - 3x + 1[/tex]